ANALISIS FINANSIAL PEMBUATAN LINE MACHINING UNTUK PRODUK COVER RIGHT CRANK CASE - Yufikar, Agwan; Hartono, Gunawarman (Industrial and Systems Engineering Assessment Journal (INASEA), 2011)
Due to the demand for motorcycles in height, PT XYZ add product variants kwb coded. PT ABC as a vendor of PT XYZ gets a chance in the manufacture of one component type is the product kwb Right Crank Case Cover. To be able to meet the demand for PT XYZ in the manufacture of products Right Crank Case Cover, PT ABC must invest in Line Machining. The purpose of this study is to determine what machining process will be chosen and the results of the feasibility of investing Line Machining will be done. Method of problem solving carried out by formulating the problem and continued with the search literature study. For data collection and research were observed directly in PT ABC. After that proceed with the processing and analysis of data using several methods used in testing the financial feasibility. The results of this research can provide information about the large value obtained from the machining cost investment plan of Line Machining. Then to provide recommendations to the management company for the feasibility of making investments Line Machining.